Monitoring Iodine Deficiency in a District Hospital, Nepal - Singh, V. K.; Joshi, A. B.; Gurung, C. K.; Pant, K. R.; Banjara, M. R. (Kathmandu University Medical Journal, 2020)
Background Iodine deficiency possesses serious threat to pregnant women and infants. During pregnancy, iodine deficiency can result in stillbirth while in infants it can lead to impaired brain development.Objective This study was conducted to assess the status of iodine deficiency among pregnant women and infants.Method Ninety seven pregnant women seeking antenatal check-up (ANC) from Chautara Hospital Sindhupalchowk were included to analyze urine iodine. Thirty one mothers and their children were followed-up for their clinical status. Additionally, the infants were assessed for their urine iodine excretion and the mothers were assessed for their awareness about iodine and iodine deficiency disorder (IDD).Result Urinary iodine excretion revealed 25.2% of pregnant women and 20% children below one year of age had insufficient iodine intake while 42.9% of pregnant women and 24% children had iodine level above normal. Almost all households were found using iodized salt, 80% respondents had heard about iodized salt, 13% mothers were aware of benefits of iodized salt, 41.9% had knowledge of iodine deficiency diseases and 38.4% cognized the source of iodine.Conclusion Though awareness about iodine and iodine deficiency disorder was satisfactory, pregnant women and children were at risk of iodine deficiency and excessive iodine disorder. Therefore, to improve health of pregnant women and newborn, their nutrition must be prioritized which ultimately will help reduce morbidity and mortality.